Pessimism and overcommitment - Claes Ek; Margaret Samahita (University College Dublin, UCD Centre for Economic Research, 2019)
Economic agents commonly use commitment devices to limit impulsive behavior in the interest of long-term goals. We provide evidence for excess demand for commitment in a laboratory experiment. Subjects are faced with a tedious productivity task and a tempting option to surf the internet. Subjects state their willingness-to-pay for a commitment device that removes the option to surf. The commitment device is then allocated with some probability, thus allowing us to observe the behavior of subjects who demand commitment but have to face temptation. We find that a significant share of the subjects overestimate their demand for commitment when compared to their material loss from facing the temptation. This is true even when we take into account the potential desire to avoid psychological costs from being tempted. Assuming risk aversion does not change our conclusion, though it suggests that pessimism in expected performance, rather than psychological cost, is the main driver of overcommitment. Our results suggest there is a need to reconsider the active promotion of commitment devices in situations where there is limited disutility from the tempting option.
Keywords: C91; D03; D91; 330; Commitment device; pessimism; self-control